An insight into the use and assessment of lower limb running prostheses in sport with a disability: A mixed method approach. Issue 1 (31st December 2016) - Dyer, Bryce
Abstract: In able-bodied sport, controversy has occasionally been caused through the adoption or introduction of sports technology. However, scant attention has specifically been paid to sport with a disability with respect to such concerns. This article therefore investigates the use of lower limb running prostheses (LLRPs) in competition by below-knee amputees. This study uses a four-phase mixed method approach to investigate the nature, use and assessment of LLRPs. The first phase conducted a statistical analysis of the sports time series data to ascertain the progression of the sport when considering the impact of sports technology. The second phase performed a stakeholder assessment of the sport using the Delphi method and provided a proposed series of guidelines for lower limb prostheses technology inclusion. The third phase assessed the behaviour of LLRPs in a competitive environment. Ultimately, the three previous phases provided information that led to the fourth phase. This phase investigated the use of a dynamic drop jump technique as an assessment strategy for further development in the future. This information would prove of intrinsic value when developing sports policy in the future.